Pengaruh Disiplin Kerja, Motivasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Pada Royal Suite Hotel Kota Balikpapan - Aliarisqi, Dita; Hasan, Syahril; Yuliani, Tutik (Jurnal GeoEkonomi, 2026)
This study aims to determine the effect of work discipline, motivation and work environment on employee job satisfaction at Royal Suite Hotel Balikpapan City. Population and sample in this research are 41 employees of Royal Suite Hotel Balikpapan City. By using total/census sampling technique so that the sample used is 41 respondents. Data collection method is done by distributing questionnaires. This research uses SmartPLS in managing data. The result of this research shows that Work Discipline variable has no effect on Job Satisfaction of Royal Suite Hotel Balikpapan City Employees. Motivation variable affects Job Satisfaction of Royal Suite Hotel Balikpapan City employees. Work Environment variable affects Job Satisfaction of Royal Suite Hotel Balikpapan City Employees.